Evaluation of a Digital Health Initiative in Illicit Substance Use: Cross-sectional Survey Study - Steph Kershaw; Louise Birrell; Hannah Deen; Nicola C Newton; Lexine A Stapinski; Katrina E Champion; Frances Kay-Lambkin; Maree Teesson; Cath Chapman (JMIR Publications, 2021)
BackgroundThe Cracks in the Ice (CITI) community toolkit was developed to provide evidence-based, up-to-date information and resources about crystal methamphetamine to Australians. Given the high rates of internet use in the community and the potential for misinformation, CITI has the potential to play an important role in improving knowledge and challenging misconceptions surrounding crystal methamphetamine. ObjectiveThis study aims to determine (1) whether the CITI toolkit is achieving its aim of disseminating evidence-based information and resources to people who use crystal methamphetamine, their family and friends, health professionals, and the general community and (2) examine the association between the use of CITI and the knowledge and attitudes about crystal methamphetamine. MethodsA cross-sectional web-based survey, open to Australian residents (aged ≥18 years), was conducted from November 2018 to March 2019. People who had previously visited the website (referred to as "website visitors" in this study) and those who had not ("naïve") were recruited. At baseline, knowledge, attitudes, and demographics were assessed. CITI website visitors then completed a series of site evaluation questions, including the System Usability Scale (SUS), and naïve participants were asked to undertake a guided site tour of a replicated version of the site before completing the evaluation questions and repeating knowledge and attitude scales. ResultsOf a total 2108 participants, 564 (26.7%) reported lifetime use of crystal methamphetamine, 434 (20.6%) were family/friends, 288 (13.7%) were health professionals, and 822 (38.9%) were community members. The average SUS score was 73.49 (SD 13.30), indicating good site usability. Health professionals reported significantly higher SUS scores than community members (P=.02) and people who used crystal methamphetamine (P<.001). Website visitors had significantly higher baseline knowledge than naïve participants (P<.001). Among naïve participants, knowledge scores increased following exposure to the website (mean 15.2, SE 0.05) compared to baseline (mean 14.4, SE 0.05; P<.001). The largest shifts in knowledge were observed for items related to prevalence, legal issues, and the effects of the drug. Stigmatizing attitude scores among the naïve group were significantly lower following exposure to CITI (mean 41.97, SE 0.21) compared to baseline (mean 44.3, SE 0.21; P<.001). ConclusionsThis study provides an innovative evaluation of a national eHealth resource. CITI is achieving its aim of disseminating evidence-based, nonstigmatizing, and useful information and resources about crystal methamphetamine to key end user groups and has received good usability scores across its target groups. Interaction with CITI led to immediate improvements in knowledge about crystal methamphetamine and a decrease in stigmatizing attitudes. CITI demonstrates the important role of digital information and support platforms for translating evidence into practice and improving knowledge and reducing stigma.